Slow Stroke Back Massage Demonstrates Greater Efficacy Compared to Core Strengthening Exercises in Reducing Dysmenorrhea among Female University Students - Syah, Irhas; Febriani, Yelva; Sari, Indah Mayang (PT. Riset Press International, 2024)
Women experiencing dysmenorrhea accompanied by abdominal cramps originating from uterine muscle contractions can lead to muscle tension and cause pain that adversely affects daily activities. This study aimed to determine the effectiveness of Slow Stroke Back Massage combined with Core Strengthening Exercise in reducing dysmenorrhea. This research employed a quantitative approach with a quasi-experimental research design. Sample collection was conducted using purposive sampling method. The study was carried out from December to January 2023, with a population of 97 individuals. A total of 30 participants were selected, with Group I receiving Slow Stroke Back Massage and Group II receiving Core Strengthening Exercise. Each group underwent the intervention eight times with two days of rest in between. The reduction in pain was measured using the Visual Analogue Scale (VAS). The average pain score before the Slow Stroke Back Massage intervention was 5.307, which decreased to 3.400 after the intervention. The p-value was 0.000, indicating a significant effect of the intervention on reducing dysmenorrheal pain. The average pain score before the Core Strengthening Exercise intervention was 5.073, which decreased to 1.780 after the intervention, with a p-value of 0.001, signifying a significant effect of the intervention on reducing dysmenorrheal pain. Based on the research findings, it can be concluded that Core Strengthening Exercise is more effective than Slow Stroke Back Massage in reducing dysmenorrheal pain in female university students.